Renal safety of lithium in HIV-infected patients established on tenofovir disoproxil fumarate containing antiretroviral therapy: analysis from a randomized placebo-controlled trial. Issue 1 (December 2017) - Decloedt, Eric; Lesosky, Maia; Maartens, Gary; Joska, John
Abstract Background The prevalence of bipolar disorder in HIV-infected patients is higher than the general population. Lithium is the most effective mood stabiliser, while tenofovir disoproxil fumarate (TDF) is frequently used as part of combination antiretroviral therapy (ART). Both TDF and lithium are associated with renal tubular toxicity, which could be additive, or a pharmacokinetic interaction may occur at renal transporters with a decrease in TDF elimination. Objective We report on the change in estimated glomerular filtration rate (eGFR) using the modification of diet in renal disease formula in participants who received ART including TDF and were enrolled in a 24 week randomised trial of lithium versus placebo in patients with HIV-associated neurocognitive impairment. Methods We included HIV-infected adults with cognitive impairment established on ART for at least 6 months with a suppressed viral load attending public sector ART clinics in Cape Town, South Africa. We excluded participants with an eGFR <60 mL/min and treated with medications predisposing to lithium toxicity. We reviewed participants weekly for the first month for adverse events followed by 4 weekly visits for renal function assessment, adverse event monitoring and adherence. Lithium dose was titrated to achieve the maintenance target plasma concentration of between 0.6 and 1.0 mmol/L. Sham lithium concentrations were generated for participants receiving placebo. Results We included 23 participants allocated to the lithium arm and 30 participants allocated to the placebo arm. Baseline characteristics were not statistically different with a mean age of 37.7 and 40.8 years, a median time on ART of 33 and 40 months and an eGFR of 139.3 and 131.0 mL/min in the lithium and placebo arms respectively. There was no statistical significant difference in the reduction in eGFR or increase in potassium between the two arms during the 24 weeks. Conclusions We found that 24-week treatment of HIV-infected patients with lithium and TDF did not result in increased nephrotoxicity. Trial registration The study was registered on the Pan African Clinical Trials Registry (PACTR) with the identifier number PACTR201310000635418. Registered 11 October 2013 before the first participant was enrolled